BSERVATION ON THE PAPER ENTITLED “SPECIAL PAIRS OF RECTANGLES AND SPHENIC NUMBER - M. A., GOPALAN; S., VIDHYALAKSHMI; THANGAM, S. AARTHY (International Journal of Multidisciplinary Research and Studies, 2019)
This paper aims at presenting pairs of rectangles representing the same sphenic number where, in each pair, the sum of the areas is 2 times sphenic number -1